DAYA TERIMA TELUR PINDANG DENGAN PENAMBAHAN BUBUK DAUN JAMBU BIJI (Psidium Guajava Linn) - Salmanuddin, Salmanuddin; Wijaya, Mohammad; Kadirman, Kadirman (Universitas Negeri Makassar, 2019)
This study aims to know the guava leaf powder concentration and level of panelist acceptance on the quality of pindang eggs produced. The research used Completely Randomized Design (CRD) with treatment of guava leaf powder solution concentration of 30%, 45% and 60%. The parameters observed in this research were water content, protein content, and hedonic value of pindang eggs. The analytical technique used in this study is the analysis of variance analyzed using SPSS version 22. The results showed the chemical quality of the pindang egg with the addition of guava leaf powder which was used in a very significant effect on the reduction in water content and the resulting proteinÂ egg pindangÂ content. Organoleptic test results on color, texture, aroma and taste most preferred by the panelist that is on the of treatment C with concentration of guava leaf powder addition 60%